Ahtithetical approach to leisure - Bretoneche Gutiérrez, Luis Alberto (2020)
Through this text, you can see antithetical opinions of the term leisure or its equivalents that have implications in knowledge, daily life, science and philosophy. The two senses that the term leisure has had over time are the negative and the positive. It is summarized, on the one hand, the negative sense given by ordinary people, Hesiod, Seneca, Michel de Montaigne, Francis Bacon, Immanuel Kant and Frederick W. Taylor, while, on the other hand, you can estimate the positive sense of the concept in Plato, Aristotle and Cicero.